PENGARUH KONSUMSI SUSU TEMPE TERHADAP KADAR HAEMOGLOBIN PADA IBU HAMIL TRIMESTER III - Novita Br Ginting Munthe; G.F Gustina Siregar; Iskandar Markus Sembiring; NURSYIDAH . (JURNAL KESMAS DAN GIZI (JKG), 2021)
Anemia in pregnancy can adversely affect the mother, especially during pregnancy, childbirth and the puerperium. The high prevalence of anemia has negative consequences such as disturbances and inhibition of growth, both body and brain cells, lack of hemoglobin in the blood resulting in a lack of oxygen being under/transferred to body cells and to the brain. Pregnant women who suffer from anemia have the possibility to experience post partum bleeding. Tempe has higher quality and nutritional value. The fermentation process in tempe will activate the phytase enzyme which can break down phytic acid. With the breakdown of phytic acid, minerals such as iron, calcium, magnesium and zinc become more available for use by the body. This study aims to determine the effect of tempeh milk consumption on increasing hemoglobin levels in pregnant women in the independent practice of midwife zuhrah hh, Samudera District, North Aceh District in 2021. The method in this study is a quasi-experimental study, the design used is one group pre-posttest design. By using the Wilcoxon test. The results showed that the average HB level in pregnant women before consuming tempeh milk was 9 gr% and 12 gr% after consuming tempeh milk. The results showed that the positive ranks value was 8.50, so it could be concluded that there was an increase in hemoglobin levels after being given tempeh milk compared to before being given tempeh milk, so the hypothesis decision was that there was a significant difference in the pre-postest respondents who were given tempeh milk. So it can be concluded that H0 is rejected and Ha is accepted. It is hoped that health workers can provide information to all pregnant women so that they can consume tempe as a daily food ingredient.